1994
DOI: 10.1111/j.1559-1816.1994.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influence of Work Environment Variables and Moderators on the Burnout Syndrome

Abstract: This study investigates the relationship between component factors of the work environment and burnout. Age, time on the job, and the intensity of religious beliefs were hypothesized to moderate the work environment/burnout linkage. The Work Environment Scale (Moos, 1986) was used to assess the work environment, and burnout was measured by the Maslach Burnout Inventory (Maslach & Jackson, 1986). Results identified peer cohesion, work pressure, supervisor support, job clarity, and autonomy as work environment v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 40 publications
1
51
0
5
Order By: Relevance
“…Many empirical studies (e.g., Leiter and Maslach, 1988;Firth and Britton, 1989;Cordes and Dougherty, 1993;Turnipseed, 1994;Wright and Bonett, 1997;Etzion et al, 1998;Maslach and Goldberg, 1998;Van Dierendonck et al, 1998;Gillespie et al, 2001;Hsieh and Chao, 2004;Gill et al, 2006;Pienaar and Willemse, 2008) have reported that burnout results in additional negative effects on individuals, including reduced satisfaction and lower levels of productivity. Burnout also impacts the organization and management by eliciting employee mistrust and discouraging teamwork.…”
Section: Burnoutmentioning
confidence: 99%
“…Many empirical studies (e.g., Leiter and Maslach, 1988;Firth and Britton, 1989;Cordes and Dougherty, 1993;Turnipseed, 1994;Wright and Bonett, 1997;Etzion et al, 1998;Maslach and Goldberg, 1998;Van Dierendonck et al, 1998;Gillespie et al, 2001;Hsieh and Chao, 2004;Gill et al, 2006;Pienaar and Willemse, 2008) have reported that burnout results in additional negative effects on individuals, including reduced satisfaction and lower levels of productivity. Burnout also impacts the organization and management by eliciting employee mistrust and discouraging teamwork.…”
Section: Burnoutmentioning
confidence: 99%
“…That is, many of the situations that counselors deal with would fit the hypothesis that their work settings give rise to stress through role conflict (e.g., difficulty, internally contradictory expectations, person-role conflict), role ambiguity (which may arise from high rates of change either in technology, in the environment, social structures in the organization, and personnel), and workload (demands). There is considerable support in the organizational literature for these notions (Barling, Kelloway, & Frone, 2005) in that many of these same constructs are integral to the literature on "burnout" in the workforce (Lacoursiere, 2001;Maslach et al, 2001;Shirom, Nirel, & Vinkur, 2006;Turnipseed, 1994;Garner, Knight, & Simpson, & Flynn, in press). For example, reports showing work stress being related to worker strain are common (e.g., Fried, Rowland, & Ferris, 1984;Faucett, 2005;Carayon & Zijlstra, 1999;Carayon, Yang, & Lee, 1995), as is work stress to worker behavior/ performance (e.g., Davidson & Cooper, 1986;Jackson, 1983;Shirom et al, 2006).…”
Section: Conceptual Background: Perceptions Of Organizational Climatementioning
confidence: 99%
“…These reflect levels of trust in counselor abilities by management and supervisors (Gelsema et al, 2006;Shoptaw, Stein, & Rawson, 2000), as well as important factors pertinent to the study of work environment (Maslach & Leiter, 1997;Turnipseed, 1994). Other dimensions of the ORC that address work environment are communication within the workplace, cohesiveness of the staff, clarity of the goals of the program, and encouragement of staff to improve treatment procedures.…”
mentioning
confidence: 99%
“…(Lee CHM et al, 2007;Park BK, 2008;Kim SJ et al, 2014). 직무 스트레스는 또한 신체 적, 심리적 건강에 문제를 야기할 뿐 아니라 업무의 질, 조 직의 효과성에도 부정적인 영향을 미친다 (Kim JH, 1992;Cordes et al, 1993;Turnipseed, 1994). Zapf et al(2006) (Hochschild, 1983;Bogner et al, 1990).…”
unclassified